Impacts of dividend policy and leverage on the probability of IPO firms to conduct SEOs: survival analysis of Hong Kong listed firms - Kamani, Mohammad Salman Akber (2022)
This study investigates whether Dividend Policy and Leverage are useful indicators to predict whether firms will conduct SEOs in the form of Rights issues and Open offers in Hong Kong. The motivation behind identifying the key factors is to educate investors on how to avoid getting hurt by high wealth transfers and negative abnormal announcement returns associated with rights issues and open offers. Unlike previous studies, this study for the first time includes censored and recurrent event data by applying a discrete-time survival analysis method to determine factors that predict the likelihood of conducting SEOs. The findings of this study demonstrate that proxies of dividend policy and leverage are statistically significant. The results also show that SEOs were conducted by firms in weak financial condition as dividend payout ratio negatively impacted the decision to conduct SEOs, while total debt-to-asset ratio had a positive relationship with the likelihood of conducting SEOs. However, dividend policy is a more useful indicator than leverage to predict whether IPO firms will conduct SEOs because there was a significant difference in dividend payout ratio between IPO firms that conducted SEOs versus IPO firms that did not conduct SEOs throughout the observation period from 2003 to 2020. Whereas the total debt-to-asset ratio did not show a significant difference consistently throughout the entire period. Thus, to avoid monetary losses associated with announcements of rights issues and open offers, investors should avoid investing in firms that are decreasing their dividend payout ratio as they have a high probability of conducting SEOs.